Selecting an Individualized Treatment Approach: The Predictive Value of Erotic Stimulation and Nocturnal Erections for Efficacy of Tadalafil and Cure in Patients With Erectile Dysfunction - Liu, Zhiwei; Wu, Tao; Ma, Shanjin; Xue, Wei; Jiang, Xiaoye; Tang, Qisheng; Ma, Jianjun (Frontiers in Endocrinology, 2022)
Purpose This study aimed to evaluate two modes of Rigiscan for predicting tadalafil response, and to identify which Rigiscan variables are the most efficient at making these predictions. Methods All patients received at least two rounds of nocturnal penile tumescence and rigidity (NPTR) testing and/or audiovisual sexual stimulation (AVSS), then completed the International Index of Erectile Function-5 (IIEF-5) questionnaire, followed by oral 5 mg tadalafil daily for 4 weeks. After a 4-week washout period, all respondents underwent an the IIEF-5 questionnaire again. ED patients were then categorized into tadalafil responders and tadalafil non-responders, who were then further divided into cured patients and uncured patients. Results When predicting tadalafil responders, the area under the curve (AUC) of NPTR was superior to that of AVSS (0.68 0.84 VS 0.69 0.73), and the predicted optimal cut-off values were DOEE60≥17.75 min in NPTR, compared to other parameters regardless of AVSS or NPTR (P<0.05). When predicting which patients would be cured, the AUC of AVSS was superior to NPTR parameters (0.77 0.81 vs 0.61 0.76), and the determined best diagnostic cut-off values were DOEE≥4.125min in AVSS, compared to other parameters regardless of AVSS or NPTR (P < 0.05). Conclusion Rigiscan was able to predict the efficacy of daily tadalafil accurately and efficiently. Its diagnostic value was at maximum when DOEE60 ≥17.75 min of NPTR in tadalafil responders and DOEE ≥ 4.125 min of AVSS in cured patients.